Dissociation free energy profiles for water and methanol on TiO2 surfaces - Sanchez, Veronica Muriel (2010)
The umbrella sampling methodology is applied in the framework of density functional theory and Car-Parrinello molecular dynamics simulations to obtain the free energy profiles for the dissociation of methanol and water on stoichiometric TiO2 surfaces. In particular, we study the dissociation of water on rutile (110) and anatase (101), and the dissociation of the O-H and C-O bonds of methanol on anatase (101). We discuss the reaction free energies and activation barriers of these processes in the light of experiments and previous simulations at zero temperature. The entropic contribution to the reaction free energy is found to be positive for the dissociation of water and negative for the dissociation of methanol. © 2010 American Chemical Society.